The Right to Petition in the Republic of Poland – New Challenges and new Solutions - Wójcicka, Ewa (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
Petitioning is one of the most fundamental rights. The right to petition is recognized not only by the constitutions of countries with rich democratic traditions, but also by those which, after many years of totalitarianism, undertook the building of new political systems after the year 1989. Poland belongs to this second group of countries, although the institution of petitioning has a long tradition and was known at the beginning of the 20th century. Real socialism and the dictate of the Union of Soviet Socialist Republics questioned the sense and need of the existence of this law. The communist authorities eliminated the notion of “petition” from legal regulations not only in Poland, but also in other satellite countries. The term “petition” was regarded as “bourgeois” and incitement to collective rebellion. After many years of discontinued existence of the institution of petition in the Polish legal system, the Constitution of the Republic of Poland restored it in 1997. The aim of this article is an attempt to analyse the right to petition specified expressly in Article 63 of the Basic Law. I am going to discuss the process of the restoration of the institution of petition into the Polish legal system as well as the changes which occurred in the works of the Constitutional Committee of the National Assembly in the years 1993-1997. I am going to present the prevailing conceptions of the right to petition, the functions of this right, the subjective and objective scope of the right to petition. In the end, I will try to answer the question of whether the present normative shape of the right to petition is understood correctly, and if not, which reforms should be introduced to adjust it to the standards and requirements of the democratic state.
Keywords: prawo do petycji; prawa polityczne; Konstytucja RP; petycja; wniosek; skarga